The EmpaTeach intervention for reducing physical violence from teachers to students in Nyarugusu Refugee Camp: A cluster-randomised controlled trial. - Camilla Fabbri; Katherine Rodrigues; Baptiste Leurent; Elizabeth Allen; Mary Qiu; Martin Zuakulu; Dennis Nombo; Michael Kaemingk; Alexandra De Filippo; Gerard Torrats-Espinosa; Elizabeth Shayo; Vivien Barongo; et al. (PLoS Medicine)
Background School-based violence prevention interventions offer enormous potential to reduce children's experience of violence perpetrated by teachers, but few have been rigorously evaluated globally and, to the best of our knowledge, none in humanitarian settings. We tested whether the EmpaTeach intervention could reduce physical violence from teachers to students in Nyarugusu Refugee Camp, Tanzania. Methods and findings We conducted a 2-arm cluster-randomised controlled trial with parallel assignment. A complete sample of all 27 primary and secondary schools in Nyarugusu Refugee Camp were approached and agreed to participate in the study. Eligible students and teachers participated in cross-sectional baseline, midline, and endline surveys in November/December 2018, May/June 2019, and January/February 2020, respectively. Fourteen schools were randomly assigned to receive a violence prevention intervention targeted at teachers implemented in January-March 2019; 13 formed a wait-list control group. The EmpaTeach intervention used empathy-building exercises and group work to equip teachers with self-regulation, alternative discipline techniques, and classroom management strategies. Allocation was not concealed due to the nature of the intervention. The primary outcome was students' self-reported experience of physical violence from teachers, assessed at midline using a modified version of the ISPCAN Child Abuse Screening Tool-Child Institutional. Secondary outcomes included student reports of emotional violence, depressive symptoms, and school attendance. Analyses were by intention to treat, using generalised estimating equations adjusted for stratification factors. No schools left the study. In total, 1,493 of the 1,866 (80%) randomly sampled students approached for participation took part in the baseline survey; at baseline 54.1% of students reported past-week physical violence from school staff. In total, 1,619 of 1,978 students (81.9%) took part in the midline survey, and 1,617 of 2,032 students (79.6%) participated at endline. Prevalence of past-week violence at midline was not statistically different in intervention (408 of 839 students, 48.6%) and control schools (412 of 777 students, 53.0%; risk ratio = 0.91, 95% CI 0.80 to 1.02, p = 0.106). No effect was detected on secondary outcomes. A camp-wide educational policy change during intervention implementation resulted in 14.7% of teachers in the intervention arm receiving a compressed version of the intervention, but exploratory analyses showed no difference in our primary outcome by school-level adherence to the intervention. Main study limitations included the small number of schools in the camp, which limited statistical power to detect small differences between intervention and control groups. We also did not assess the test-retest reliability of our outcome measures, and interviewers were unmasked to intervention allocation. Conclusions There was no evidence that the EmpaTeach intervention effectively reduced physical violence from teachers towards primary or secondary school students in Nyarugusu Refugee Camp. Further research is needed to develop and test interventions to prevent teacher violence in humanitarian settings. Trial registration clinicaltrials.gov (NCT03745573).